Reform at the top: what’s next for the WTO? A second life? A socio-political analysis - Drache, Daniel (Oñati Socio-Legal Series, 2011)
A fundamental change is taking place in the global economy, and the standoff in the Doha Round has raised many questions about the World Trade Organization’s troubled architecture (Khor, 2009). So far, the quest for renewed policy coherence in the rules-based multilateral system has produced stalemate rather than reform. The analysis that follows explores the proposition that, without the metaphoric ‘knife at its throat’ to shock it to its senses, the WTO will continue in the short term to be trapped by its existing architecture. There is no coherent reform-minded movement supported by a critical number of states to instigate a change in the way the WTO does business. The paper looks at the following idea: with many states pursuing new policy frames to enhance their strategic interests, the second life of the WTO will be dramatically different from the present configuration. A lengthy trade pause is a certainty. Four options of what the WTO will become are examined. The conclusion is that as a governance body the WTO faces gradual and likely irreversible decline. It will have a smaller remit, be prone to mini-multilateralism and have to learn to live with a proliferation of regional trade agreements.